2020
DOI: 10.4257/oeco.2020.2403.05
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF PHENOL ON Astyanax bifasciatus AND Daphnia magna

Abstract: In the present study, we investigated the possible toxic effects of phenol on two bioindicators: the fish Astyanax bifasciatus (Characiformes; Characidae) and the crustacean Daphnia magna (Cladocera; Daphnidae). We performed bioassays with A. bifasciatus (96 h and 15 days of exposure) and D. magna (48 and 96 h of exposure). The bioindicator organisms were exposed to the following concentrations of phenol: 0.003 mg L-1 , 0.01 mg L-1 , 0.03 mg L-1 , 0.06 mg L-1 , and 0.1 mg L-1 ; and the control group was mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Macêdo et al (2021) concluded that 35 μg L −1 of total phenols could be produced by AR and MR. Despite falling below the recommended limit of 0.5 mg L −1 by CONAMA 430 (2011) and being lower than the concentration range (mg L −1 ) that caused effects on fish (L. K. Wang & Wang, 2024), it exceeded the concentration known to cause effects on Daphnia magna (3 μg L −1 ) (Lehun et al, 2020). Consequently, the presence of phenol may contribute to the residual toxicity observed in the AR and MR effluents.…”
Section: Discussionmentioning
confidence: 94%
“…Macêdo et al (2021) concluded that 35 μg L −1 of total phenols could be produced by AR and MR. Despite falling below the recommended limit of 0.5 mg L −1 by CONAMA 430 (2011) and being lower than the concentration range (mg L −1 ) that caused effects on fish (L. K. Wang & Wang, 2024), it exceeded the concentration known to cause effects on Daphnia magna (3 μg L −1 ) (Lehun et al, 2020). Consequently, the presence of phenol may contribute to the residual toxicity observed in the AR and MR effluents.…”
Section: Discussionmentioning
confidence: 94%